Pengembangan e-book Mlali “Mlajah Basa Bali” dalam Pembelajaran Aksara Bali - Kartika Sari, Ni Ketut Tirta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This research is on the development of e-books as a teaching medium in learning Balinese script. This research focuses on the influence of the MLALI “Mlajah Basa Bali” e-book on the learning activities of Balinese script students at the junior high school level by optimizing technological developments. The purpose of developing this e-book in learning Balinese script is to help students in the learning process by facilitating the necessary learning facilities. This research is a Research and Development (R&D) research with the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). Data collection methods in this study include classroom observation, interviews, and document analysis. The results of the study used a descriptive qualitative method. The product development in the form of an e-book was tested on grade IX students at SMP PGRI 2 Denpasar with the following research results: (1) several students had difficulty accessing MLALI e-book